Restart of Hospitality and Tourism: System Dynamics and Scenario-Based Modelling - Mattyašovská, Jitka (Academica Turistica - Tourism and Innovation Journal, 2022)
A tourism destination is defined as an open, complex, and adaptive system, in which numerous relations in the economic, social, and environmental spheres are generated. This paper aims to define a system dynamics model of tourism destination as a complex system and to identify future behaviour of the system after the restart of tourism in the post-covid-19 era. The main methodological approaches were system dynamics and simulation modelling. The case of a complex tourism system in the South Bohemia Region, the Czech Republic, in the form of a Stocks and Flows Diagram (sfd) is presented in this paper, focusing on the business activities at this tourism destination. The simulation results show the future behaviours of the system in various scenarios and compare the development of several economic indicators. Three possible future scenarios of a restart of the hospitality and tourism industry are compared with the theoretical situation without covid-19 disease. The proposed system dynamics model contributes to the current theory of tourism destination management systems and can be used practically by destination managers for destination planning and to formulate destination strategies. Keywords: system dynamics, simulation modelling, tourism destination, destination management